MANAJEMEN MUTU DAN JAMINAN MUTU SEKOLAH UNGGUL - Hasanah, Muwahidah Nur (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2019)
A superior school is a school developed to achieve educational excellence, the term superior is also called favorite, model, model and plus. The actual flagship school, is a school that was built jointly by all school members, not only by the authorities of education. Excellence can be achieved if all school resources are utilized optimally. "This means that teaching staff, administrative staff, curriculum developers, school principals, and school guards must be actively involved, because these resources will create a school climate that is able to shape school excellence. " The main key to superior schools is excellence in service to students by providing opportunities to develop student potential as optimal as possible, and balanced (tawazun).